Normalized LST Is an Efficient Biomarker for Homologous Recombination Deficiency and Olaparib Response in Ovarian Carcinoma - Christinat Yann; Ho Liza; Clément Sophie; Genestie Catherine; Sehouli Jalid; Cinieri Saverio; Gonzalez Martin Antonio; Denison Ursula; Fujiwara Keiichi; Vergote Ignace; Tognon Germana; Hietanen Sakari; et al. (United States, 2025)
Purpose
The efficiency of the Myriad Homologous Recombination Deficiency (HRD) test to guide the use of poly (ADP-ribose) polymerase (PARP) inhibitors has been demonstrated in several phase III trials. However, a need exists for alternative clinically validated tests.
Methods
A novel biomarker for HRD was developed using The Cancer Genome Atlas database and, as part of the ENGOT HRD European Initiative, applied to 469 samples from the PAOLA-1/ENGOT-ov25 trial. Results were compared with the Myriad myChoice Genomic Instability Score (GIS) with respect to the progression-free survival in the olaparib + bevacizumab and placebo + bevacizumab arms.
Results
Analysis of the TCGA cohort revealed that a normalization of the number of large-scale state transitions by the number of whole-genome doubling events allows a better separation and classification of HRD samples than the GIS. Analysis of the PAOLA-1 samples, using the Geneva test (OncoScan + nLST), yielded a lower failure rate (27 of 469 v 59 of 469) and a hazard ratio of 0.40 (95% CI, 0.28 to 0.57) compared with 0.37 for Myriad myChoice (BRCAm or GIS+) in the nLST-positive samples. In patients with BRCAwt, the Geneva test identified a novel subpopulation of patients, with a favorable 1-year PFS (85%) but a poor 2-year PFS (30%) on olaparib + bevacizumab treatment.
Conclusion
The proposed test efficiently separates HRD-positive from HRD-negative patients, predicts response to PARP inhibition, and can be easily deployed in a clinical laboratory for routine practice. The performance is similar to the available commercial test, but its lower failure rate allows an increase in the number of patients who will receive a conclusive laboratory result.